1999
DOI: 10.1021/tx990003t
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Chemistry of Green Tea Catechins. Identification of Products of the Reaction of (−)-Epigallocatechin Gallate with Peroxyl Radicals

Abstract: (-)-Epigallocatechin gallate (EGCG), isolated from green tea, displays antioxidant properties and is thought to act as an antioxidant in biological systems. However, the specific mechanisms of its antioxidant actions remain unclear. In this study, we have isolated and identified for the first time two reaction products of EGCG derived from its reaction with peroxyl radicals generated by thermolysis of the initiator 2,2'-azobis(2,4-dimethylvaleronitrile) (AMVN). The products include a seven-membered B-ring anhy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
118
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(125 citation statements)
references
References 28 publications
7
118
0
Order By: Relevance
“…4). The same model fermentation experiment yielded another known dimer (15) (Tanaka et al, 2002b), which has recently been reported as an oxidation product obtained by treatment of 4 with a radical initiator in an organic solvent (Valcic et al, 1999) and with peroxidase-H 2 O 2 . Besides production of theaflavins, formation of these dimeric products from epigallocatechin and its gallate is an alternative major metabolic pathway of tea catechins.…”
Section: Formation Of Epigallocatechin Dimer Quinonesmentioning
confidence: 55%
See 1 more Smart Citation
“…4). The same model fermentation experiment yielded another known dimer (15) (Tanaka et al, 2002b), which has recently been reported as an oxidation product obtained by treatment of 4 with a radical initiator in an organic solvent (Valcic et al, 1999) and with peroxidase-H 2 O 2 . Besides production of theaflavins, formation of these dimeric products from epigallocatechin and its gallate is an alternative major metabolic pathway of tea catechins.…”
Section: Formation Of Epigallocatechin Dimer Quinonesmentioning
confidence: 55%
“…However, the major part of these metabolites probably derive from epigallocatechin (2) and its gallate (4), because these two catechins together account for over 70% of the total tea catechins in fresh tea leaves. There have been a number of reports on enzymatic and non-enzymatic oxidation of epigallocatechin and its gallate, and most of them have suggested that oxidation and subsequent intermolecular condensation between two pyrogallol B-rings dominantly occurred (Hashimoto et al, 1988;Tanaka et al, 2001;Tanaka et al, 2002b;Valcic et al, 1999;Zhu et al, 2000). In black tea, the most important metabolites derived from 2 and 4 are theasinensins (11), in which pyrogallol rings of two molecules of epigallocatechin or its gallate are linked through the C-C bond.…”
Section: Formation Of Epigallocatechin Dimer Quinonesmentioning
confidence: 99%
“…Previous studies on the antioxidative property of (À)-epigallocatechin-3-gallate have shown both the trapping effect of ROS as well as the inhibitory effect of lipid peroxidation (38). However, after neutralizing the peroxyl or other radicals, (À)-epigallocatechin-3-gallate itself could be converted to phenoxyl radical (39).…”
Section: Discussionmentioning
confidence: 97%
“…The exact mechanisms of action of green tea polyphenols remain obscure, but it is known that these substances possess antioxidative capacity derived from their ability to scavenge reactive oxygen species and trap hydroxyl and peroxyl radicals. The in vitro antioxidant capacity of teas and tea polyphenols has been assessed using several different approaches [4][5][6]. Moreover, antioxidative effects of tea polyphenols have been reported in humans [7][8][9].…”
Section: Introductionmentioning
confidence: 99%